Early Career South African Occupational Therapists' Perceptions of Person-Environment Fit in Work-Life Areas That Influence Work Stress - Patricia de Witt; Morgann Bruce; Marica Botha; Denise Franzsen (Hindawi-Wiley, 2024)
Conclusion: Workload impacted workplace-related stress in respondents with scores below the norm on the AWS for this work-life area. Although some work-related factors affected workplace-related stress, the overall scores for the other work-life areas were above the norm, with only respondents in public service settings and in the field of physical rehabilitation reporting low work environment fit.